Penerapan Model Pembelajaran Tipe Teams Games Tournament untuk Meningkatkan Kaektifan Belajar Bahasa Arab - Sri Wahyu Ningsih; Friscilla Wulan Tersta; Sahrizl Vahlepi (Diwan: Jurnal Bahasa dan Sastra Arab, 2024)
This classroom action research aims to increase student learning activity through the Teams Games Tournament (TGT) learning model in Arabic language subjects in class III MIS Ihsaniyah, Jambi City. Data collection in this research used observation and documentation techniques. The data analysis technique used is quantitative and qualitative descriptive. The results of this research indicate that the application of the Teams Games Tournament (TGT) type cooperative learning model can increase the learning activity of class III MIS Ihsaniyah students in Arabic subjects. This increase is shown in the average score of pre-action learning activity, which was 43.29, increasing to 57.44 in cycle I and 71.33 in cycle II. Meanwhile, the percentage of activity in learning Arabic before the action was 29.03%, increasing to 54.84% in cycle I and 80.65% in cycle II. Because the completion criteria have been achieved, namely a minimum average score of 70 and a minimum student completion percentage of 75%, this research is considered successful.